2014
DOI: 10.1136/gutjnl-2014-308041
|View full text |Cite
|
Sign up to set email alerts
|

TG1050, an immunotherapeutic to treat chronic hepatitis B, induces robust T cells and exerts an antiviral effect in HBV-persistent mice

Abstract: ObjectiveTo assess a new adenovirus-based immunotherapy as a novel treatment approach to chronic hepatitis B (CHB).MethodsTG1050 is a non-replicative adenovirus serotype 5 encoding a unique large fusion protein composed of a truncated HBV Core, a modified HBV Polymerase and two HBV Envelope domains. We used a recently described HBV-persistent mouse model based on a recombinant adenovirus-associated virus encoding an over length genome of HBV that induces the chronic production of HBsAg, HBeAg and infectious HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 49 publications
2
65
0
2
Order By: Relevance
“…TG1050 is a non-replicative adenovirus serotype 5 encoding a unique large fusion protein composed of a truncated HBV core, a modified HBV polymerase, and two envelope domains [29]. TG1050 demonstrated HBsAg seroconversion in persistently infected mouse models [30].…”
Section: Therapeutic Vaccinesmentioning
confidence: 99%
“…TG1050 is a non-replicative adenovirus serotype 5 encoding a unique large fusion protein composed of a truncated HBV core, a modified HBV polymerase, and two envelope domains [29]. TG1050 demonstrated HBsAg seroconversion in persistently infected mouse models [30].…”
Section: Therapeutic Vaccinesmentioning
confidence: 99%
“…Preclinical study indicated that TG1050 could induce robust and long-lasting HBV-specific T cells and exert an antiviral effect in HBV-persistent mice. 73 The sponsor of TG1050, Transgene Tasly, is initiating a doubleblind, randomized, placebo-controlled, multi-cohort Phase 1/ 1b trial in patients to assess the safety and tolerability of TG-1050. Currently, the study is recruiting participants (ClinicalTrials.gov, Identifier: NCT02428400).…”
Section: Dna-based Vaccinesmentioning
confidence: 99%
“…Les données récentes portant sur l'immunité anti-VHB au cours de l'infection chronique suggèrent que les approches vaccinales devront prendre en compte la situation complexe d'immunotolérance qui est induite par les fortes charges antigéniques présentes dans le sérum des patients ainsi que la présence de cellules T anti-VHB dont les fonctions sont fortement altérées [39]. De nouveaux vecteurs viraux ont ainsi été déve-loppés, comme ceux utilisant l'adénovirus, et les cibles antigéniques ont été élargies afin d'inclure la protéine de capside et la polymérase virale [40]. Pour tenter de contrecarrer les mécanismes d'épuisement ou d'inhibition des cellules T, des anticorps appelés « checkpoint inhibitors » (inhibiteurs de points de blocage) ayant fait leurs preuves dans le domaine de l'immunothérapie du cancer, sont en cours d'essais dans des modèles animaux en combinaison avec des vaccins ADN [41].…”
Section: La Vaccination Contre L'hépatite B : Une Approche Thérapeutiunclassified